Higher Rates of Mortality but Not Morbidity Follow Intracranial Mechanical Thrombectomy in the Elderly - Loh, Y. (AJNR Am J Neuroradiol, 2010)
BACKGROUND AND PURPOSE: Mechanical thrombectomy is a promising means of recanalizing acute cerebrovascular occlusions in certain situations. We sought to determine if increasing age adversely affects prognosis. MATERIALS AND METHODS: We reviewed all Merci thrombectomy cases and compared patients younger than 80 years of age with older individuals. We compared these 2 age groups with respect to recanalization rates, hospital LOS, hemorrhagic transformation, and death and disability on discharge. RESULTS: Elderly patients were more likely to die from their stroke than those younger than 80 years of age, regardless of recanalization success (48% versus 15%; OR, 5.5; 95% CI, 2.1–14.1). Among survivors, there was no difference in the probability of having a good functional outcome (mRS, ≤2) by discharge (38% versus 40%; OR, 0.9; 95% CI, 0.3–2.8). Hemorrhagic transformation did not vary between age groups. CONCLUSIONS: Among patients undergoing mechanical thrombectomy for acute cerebrovascular occlusions, increased age conveys a higher rate of stroke-related death, but disability at discharge in this group is similar to that of younger survivors.